2019
DOI: 10.1515/biol-2019-0060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rhamnolipids on microbial biomass content and biochemical parameters in soil contaminated with coal tar creosote

Abstract: The objective of the present study was to compare the effect of rhamnolipids on the microbial biomass content and the activity of dehydrogenases (DHA), acid phosphatase (ACP), alkaline phosphatase (ALP), and urease (URE) in soil contaminated with two types of coal tar creosote: type C and type GX-Plus. The experiment was carried out on samples of sandy clay loam under laboratory conditions. Coal tar creosote was added to soil samples at a dose of 0 and 10 g·kg−1 DM, along with rhamnolipids at a dose of 0, 10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the chemical composition and other environmental factors such as pH and temperature have an influence on the biodegradation process and enzymatic activity. The decrease in enzyme activity observed in the initial period of the experiment, especially DHA, may result from disturbances in soil air conditions [39]. It is also worth noting the quantitative and qualitative composition of indigenous microflora.…”
Section: Corgmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the chemical composition and other environmental factors such as pH and temperature have an influence on the biodegradation process and enzymatic activity. The decrease in enzyme activity observed in the initial period of the experiment, especially DHA, may result from disturbances in soil air conditions [39]. It is also worth noting the quantitative and qualitative composition of indigenous microflora.…”
Section: Corgmentioning
confidence: 94%
“…Contamination of the soil with light crude oil fractions mainly stimulated the activity of oxidoreductases [3], but inhibited the activity of hydrolases [37], which was also confirmed by the results of the present study. On the other hand, the introduction of heavier crude oil fractions such as diesel oil, spent engine oil, or coal tar creosote into the soil negatively impacted the activity of all soil enzymes [9,17,31,38,39]. An analysis of the effect of Fyre-Zyme preparation (IF FZ ) on DHA in the uncontaminated and petrol contaminated soil, based on the values of the enzyme coefficients, indicated that the values were close to 1, on all measurement dates, for each type of preparation application.…”
Section: Corgmentioning
confidence: 99%
See 1 more Smart Citation